Evaluation of a new mineral and trace metal supplement for use with synthetic diets. Issue 1 (January 1977) - Lawson, M S; Clayton, B E; Delves, H T; Mitchell, J D
Abstract : In an earlier study (Alexander et al., 1974) it was shown that the mineral mixture used in association with a synthetic diet was deficient in zinc, copper, iron, and manganese. A new mixture containing appropriately increased amounts of these trace metals has now been evaluated by means of metabolic balance studies carried out on children with phenylketonuria. This new mixture was shown to be satisfactory for zinc, copper, and iron, but minor changes have been recommended for manganese.